2022
DOI: 10.3390/polym15010029
|View full text |Cite
|
Sign up to set email alerts
|

Viable Properties of Natural Rubber/Halloysite Nanotubes Composites Affected by Various Silanes

Abstract: Natural rubber (NR) is incompatible with hydrophilic additives like halloysite nanotubes (HNT) due to their different polarity. The silane coupling agent is the ideal component to include in such a compound to solve this problem. Many types of silane are available for polymer composites depending on their functionalities. This work aimed to tune it to the composite based on NR and HNT. Four different silanes, namely Bis[3- (Triethoxysilyl)Propyl]Tetrasulfide (TESPT), 3-Aminopropyl triethoxysilane (APTES), N-[3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In this study, we selected three silane coupling agents with different functional groups (see Table 1 ) to modify sepiolite. Our modification mechanism [ 38 , 39 , 40 ] involved the hydrolysis of Si–O–C 2 H 5 in the silane coupling agent and the subsequent condensation of hydroxyl groups on the surface of sepiolite, with C=C in VTES, -HS- in MPTES, and –S 4 – in TESPT all able to participate in the vulcanization process of natural rubber and form strong chemical bonds. Hydrolysis of silane coupling agents is known to be slow, often requiring the addition of acid to promote hydrolysis [ 41 , 42 ] and improve the efficiency of hydroxyl condensation with the inorganic filler surface.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we selected three silane coupling agents with different functional groups (see Table 1 ) to modify sepiolite. Our modification mechanism [ 38 , 39 , 40 ] involved the hydrolysis of Si–O–C 2 H 5 in the silane coupling agent and the subsequent condensation of hydroxyl groups on the surface of sepiolite, with C=C in VTES, -HS- in MPTES, and –S 4 – in TESPT all able to participate in the vulcanization process of natural rubber and form strong chemical bonds. Hydrolysis of silane coupling agents is known to be slow, often requiring the addition of acid to promote hydrolysis [ 41 , 42 ] and improve the efficiency of hydroxyl condensation with the inorganic filler surface.…”
Section: Introductionmentioning
confidence: 99%
“…The morphology study showed that the size of NBR droplets in TPE nanocomposites was reduced by the presence of halloysite and that its size is even smaller with the modified HNT. More recently, Hayeemasae et al [29] evaluated the grafting effect of respectively the bis Propyl]Tetrasulfide (TESPT), the 3-Aminopropyl triethoxysilane (APTES), the N- Propyl] Ethylenediamine (AEAPTMS), and the Vinyltrimethoxysilane (VTMS) on both the dispersion of HNT and coupling reactions between natural rubber (NR) and HNT. It was observed that the mechanical properties of the corresponding materials were improved by introducing silanes and even more using AEAPTMS.…”
mentioning
confidence: 99%